The International Classification of Functioning, Disability and Health (ICF): Opportunities and challenges to the use of ICF for occupational therapy. Issue 2 (October 2015) - Prodinger, Birgit; Darzins, Susan; Magasi, Susan; Baptiste, Sue
Abstract : The occupational therapy community has been receptive to the World Health Organisation's International Classification of Functioning, Disability and Health (ICF) published in 2001. Building upon results of a survey (2008–2009) and subsequent workshop (2010) conducted by the World Federation of Occupational Therapists on the use and utility of the ICF for occupational therapists, this paper addresses some of the opportunities and challenges to strengthening the use of the ICF in occupational therapy practice. Attaining further clarity on the relationship of occupational therapy concepts and the ICF and developing crosswalk tables to exemplify linkages between occupational therapy terminology and the ICF will strengthen utility of the ICF for occupational therapy. Enhanced clarity about the concepts within occupational therapy that correspond to the ICF will ultimately assist other professions and disciplines in their understanding about occupational therapy and occupational therapists' roles in health and related systems.